TINDAK PIDANA KORUPSI SEBAGAI KEJAHATAN LUAR BIASA (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2022)
The criminal act of corruption is a part of a special crime in addition to having certain specifications that are different from common criminal acts. Corruption Law is a rule that has special characteristic, both concerning Formal Criminal Law (Criminal Justice System) and Material (Substance). The legal consequences of an act being categorize as criminal act of corruption, are include: The institution that handles the corruption case, the evidence system in the corruption act has a reversed system which trait limited or balanced, and in terms of punishment. The purpose of this paper is to provide a knowledge of how to implicate a criminal act as a criminal act of corruption. The purpose of this paper is to provide a knowledge of how to implicate a criminal act as a criminal act of corruption.